2017
DOI: 10.2337/db17-0816
|View full text |Cite
|
Sign up to set email alerts
|

Novel lncRNA Erbb4-IR Promotes Diabetic Kidney Injury in db/db Mice by Targeting miR-29b

Abstract: Transforming growth factor-β/Smad signaling plays an important role in diabetic nephropathy. The current study identified a novel Smad3-dependent long noncoding RNA (lncRNA) Erbb4-IR in the development of type 2 diabetic nephropathy (T2DN) in mice. We found that Erbb4-IR was highly expressed in T2DN of mice and specifically induced by advanced glycosylation end products (AGEs) via a Smad3-dependent mechanism. The functional role of Erbb4-IR in T2DN was revealed by kidney-specific silencing of Erbb4-IR to prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
170
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(182 citation statements)
references
References 36 publications
5
170
2
Order By: Relevance
“…The lncRNAs ENSRNOG00000037522 and LINC01619 have been reported to participate in podocyte injury in DN [34,35]. Further, Erbb4-IR is reportedly a Smad3-dependent lncRNA that promotes renal fibrosis in type 2 DN [36]. The lncRNA Gm4419 has been reported to regulate inflammation in DN [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lncRNAs ENSRNOG00000037522 and LINC01619 have been reported to participate in podocyte injury in DN [34,35]. Further, Erbb4-IR is reportedly a Smad3-dependent lncRNA that promotes renal fibrosis in type 2 DN [36]. The lncRNA Gm4419 has been reported to regulate inflammation in DN [13].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that lncRNAs are involved in various diseases, including DN [28][29][30][31]. Two lncRNAs, ENSMUST00000147869 and CYP4B1-PS1-001, have recently been reported to regulate MCs proliferation and fibrosis induced by DN [29,32].…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study demonstrated that the origin of a novel lncRNA could be identified by a combination of fluorescent in situ hybridization (FISH) and immunohistochemistry (IHC) staining on diabetic injured kidney section (Sun et al . ) (Fig. ).…”
Section: Introductionmentioning
confidence: 93%
“…More importantly, silencing of renal Erbb4‐IR significantly inhibited the expression of collagen I in both diabetic‐ and obstructive‐injured kidneys in vivo (Sun et al . ; Feng et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation